2003
DOI: 10.1029/2003wr002472
|View full text |Cite
|
Sign up to set email alerts
|

The fracture flow equation and its perturbation solution

Abstract: [1] This work derives the fracture flow equation from the two-dimensional steady form of the Navier-Stokes equation. Asymptotic solutions are obtained whereby the perturbation parameter is the ratio of the mean width over the length of the fracture segment. The perturbation expansion can handle arbitrary variation of the fracture walls as long as the dominant velocity is in the longitudinal direction. The effect of the matrix-fracture interaction is also taken into account by allowing leakage through the fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 15 publications
4
29
0
1
Order By: Relevance
“…As the condition R e > 15 was found in all the geometries that we considered (Figures , and ), One can generalize this result for 2D fractures where the aperture varies along the flow direction.Furthermore, our numerical analyses show that the relative error does not change as a function of R e in the case of parallel walls. This is in agreement with the analytical results of Basha and El‐Asmar () and Nizkaya () who found that inertial terms are null in the first and second order terms of the N S expansion solution. On the other hand, this error is maximum when the phase shift between the two walls Δ x is maximum.In all cases, the relative error between the L C L and N S solutions for higher R e increases with the increase of ε .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As the condition R e > 15 was found in all the geometries that we considered (Figures , and ), One can generalize this result for 2D fractures where the aperture varies along the flow direction.Furthermore, our numerical analyses show that the relative error does not change as a function of R e in the case of parallel walls. This is in agreement with the analytical results of Basha and El‐Asmar () and Nizkaya () who found that inertial terms are null in the first and second order terms of the N S expansion solution. On the other hand, this error is maximum when the phase shift between the two walls Δ x is maximum.In all cases, the relative error between the L C L and N S solutions for higher R e increases with the increase of ε .…”
Section: Discussionsupporting
confidence: 92%
“…H h and H 0 were compared to estimate the conditions under which the L C L , developed with respect to the hydraulic aperture H h , can be replaced by the C L , developed with respect to the mean aperture H 0 . Analytical expressions of H h based on Reynolds equation (or the zeroth order solution of the N S equations) exist for specific geometries, such as fractures having mirror‐symmetric walls (Zimmerman et al ), parallel and shifted walls (Basha & El‐Asmar, ), and non‐identical shifted walls (Nizkaya, ). These expressions show that H h deviates from H 0 and depends on the fracture geometry.…”
Section: Discussionmentioning
confidence: 99%
“…However, the assumption of the Cubic Law and its local validity may be acceptable only when the flow is largely laminar, and might not be able to provide adequate support for investigating the impacts of surface roughness on energy and mass transport processes in natural fractures, as reported in literature with both laboratory experiments and numerical simulations (e.g. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]). …”
Section: Background and Motivationmentioning
confidence: 99%
“…The issue of inertial term was investigated by Basha and ElAsmar [11] in which a steady state NSE was solved analytically, using perturbation solutions, for idealized rock fracture geometries formed by regularly shaped sinusoidal wavy 2D smooth profiles with different relative positions or two smooth and nonparallel planar or slightly curved profiles. The derived perturbation solutions consist of a leading-order approximation of Reynolds lubrication approximation and higher-order terms representing effects of amplitude and frequency of the asperities and the inertial term.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Unfortunately, the full NSE is often too difficult to solve, either analytically or numerically (Zimmerman and Yeo, 2000). As a result, only a handful of studies have been reported on the numerical simulation of the NSE in an SF (Brush and Thomson, 2003; Al‐Yaarubi et al , 2005; Cardenas et al , 2007) and even fewer studies on the analytical solutions of the NSE in an SF (Hasegawa and Izuchi, 1983; Basha and El‐Asmar, 2003). Therefore, various approximations are usually made, which reduce the NSE to a simplified equation.…”
Section: Introductionmentioning
confidence: 99%